Leptin mediates the relationship between fat mass and blood pressure: The Hamamatsu School-based health study. Issue 12 (March 2019) - Fujita, Yuki; Kouda, Katsuyasu; Ohara, Kumiko; Nakamura, Harunobu; Iki, Masayuki
Abstract : Abstract: Animal studies have shown that leptin mediates the association between obesity and hypertension. However, only a few studies have assessed this relationship in population-based epidemiological studies. This study aimed to determine whether leptin mediates the relationship between body fat and blood pressure in school-aged children. A cross-sectional survey was conducted among school-aged children in Hamamatsu, Japan. Body fat was measured using dual-energy X-ray absorptiometry. Height-normalized index of fat mass (fat mass index) was calculated by dividing fat mass by height squared. Serum leptin levels were measured by enzyme-linked immunosorbent assay. Multiple regression analysis was used to evaluate relationships between body fat, serum leptin levels, and blood pressure. The mediating effect of leptin on the association between body fat and blood pressure was assessed by causal mediation analysis and regression analysis. Both fat mass index and leptin were significantly and positively associated with blood pressure. Fat mass index was also strongly associated with serum leptin levels. Body fat and blood pressure were no longer associated after adjusting for leptin. These findings suggest that the association between body fat and blood pressure is mediated by leptin. Of the total effect of fat mass index on blood pressure, the mediating effect of leptin accounted for 78.6% ( P = .03) in boys and 42.2% ( P = .11) in girls. Our findings suggest that body fat is associated with blood pressure, and this association is mediated by leptin. Thus, leptin acts as a mediator that links body adiposity with blood pressure elevation in school-aged children.